Contract Enforcement and R&D Investment - Martin Watzinger; Michael Seitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this article we study the relation between the quality of contract enforcement and R&D investment across countries and industries. If companies invest successfully in R&D they are open for exploitation by their supplier if supply contracts are not enforceable. This hold-up problem can reduce the incentive to invest in R&D exante. In line with this theoretical idea we find in the empirical analysis that R&D investment increases with the quality of the judicial system. This effect is particularly strong in industries which rely more on contracts to acquire input and in which it is harder to vertically integrate.
Keywords: O30; O43; P48; 330